Gestión de ventas en el comercial prieto del cantón Babahoyo periodo 2020 -2021. - Cabrera Zambrano, Carlos Javier (2022)
The present case study is related to the research line of the commerce career called Marketing and Marketing, the objective of this research is to know the factors that influence the sales management of the commercial Prieto of the city of Babahoyo for which Qualitative methodology was used to produce descriptive data: people's own words, spoken or written, and observable behavior. Research methods are also used, such as the scientific one, from which reliable and valid knowledge can be obtained, the documentary method that is responsible for collecting and selecting information through the reading of documents, books, magazines, recordings, filming, newspapers, bibliographies etc in addition to applying the inductive method in the investigation that is used to analyze the observed phenomenon. To obtain the information, the survey technique was applied and data was collected through the previously designed questionnaire, without modifying the environment or the phenomenon where the information is collected, the questionnaire was applied to the 6 employees with whom Prieto de la Babahoyo city.